Peningkatan Potensi Petani Nanas melalui Program Pendampingan Pembuatan dan Pemasaran Sambal Nanas - Ika Nurfitriani; Khairan (Yayasan Literasi Altruis Khatulistiwa, 2026)
Manggis Village, Ngancar District, Kediri Regency is one of the largest pineapple producers in East Java, but the abundance of pineapples in the village has not been optimized by the community due to a lack of innovation in how to process pineapples into products with high selling value. Furthermore, the community lacks understanding of how to market processed pineapple products. They prefer to sell the pineapples harvested from their plantations directly at low prices without processing them to increase their selling price and community income. Therefore, innovation is needed to process pineapples into products with high selling value. Using the PAR approach, the goal of this program is for the community to be able to optimize their harvest into products with higher selling prices and to better understand how to market these products. The implementation of activities includes: (1) socialization of increasing pineapple processing yields (2) training in making pineapple sambal (3) formation of SME groups (4) ongoing assistance and marketing training. The result of this program is the creation of a pineapple sambal product named “Sambal Nanas Khas Ngancar” with very attractive packaging and labeling. The final outcome of this program can contribute to enhancing the capacity of MSME human resources, expanding market access, and increasing farmers’ income potential through the diversification of pineapple-based processed products rooted in local potential.